2022
DOI: 10.1038/s41598-022-11322-5
|View full text |Cite
|
Sign up to set email alerts
|

Food deprivation alters reproductive performance of biocontrol agent Hadronotus pennsylvanicus

Abstract: Diet can influence parasitoid reproductive performance, and therefore, the efficacy of biocontrol programs. We evaluated the influence of food deprivation on the reproductive fitness and behavior of the egg parasitoid Hadronotus pennsylvanicus (Hymenoptera: Scelionidae), a prospective biocontrol agent for Leptoglossus zonatus (Heteroptera: Coreidae). Newly emerged female parasitoids were mated and provided host eggs every other day while being provisioned with various honey diet regimes or a consistent supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…Behavioral tests with parasitoids fed on glucose, sucrose, or fructose showed that sugar-fed parasitoids spent more time in drumming and oviposition behaviors, while starved parasitoids provided with only water spent more time walking and resting, which is similar with Straser et al's findings for another egg parasitoid, Hadronotus pennsylvanicus (Ashmead) [6]. Some studies, however, have shown that starvation can enhance parasitoid egg-laying behavior, causing wasps to lay their eggs more rapidly, improving their fitness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Behavioral tests with parasitoids fed on glucose, sucrose, or fructose showed that sugar-fed parasitoids spent more time in drumming and oviposition behaviors, while starved parasitoids provided with only water spent more time walking and resting, which is similar with Straser et al's findings for another egg parasitoid, Hadronotus pennsylvanicus (Ashmead) [6]. Some studies, however, have shown that starvation can enhance parasitoid egg-laying behavior, causing wasps to lay their eggs more rapidly, improving their fitness.…”
Section: Discussionsupporting
confidence: 86%
“…In agricultural Insects 2024, 15, 245 2 of 11 ecosystems, the quality and availability of resources for adult parasitoids vary greatly over time and space. Food deprivation or feeding on poor quality foods can affect the longevity, parasitism rate, and parasitic behavior of female parasitoids, reducing their potential impact as biological control agents [5,6].…”
Section: Introductionmentioning
confidence: 99%